2019
DOI: 10.1037/spy0000147
|View full text |Cite
|
Sign up to set email alerts
|

Challenge and threat states, performance, and attentional control during a pressurized soccer penalty task.

Abstract: The University of Gloucestershire accepts no liability for any infringement of intellectual property rights in any material deposited but will remove such material from public view pending investigation in the event of an allegation of any such infringement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 44 publications
3
39
0
Order By: Relevance
“…Some contemporary challenge and threat theory (such as the TCTSA) does not include coping in its Lazarusian form (i.e., emotion focused and problem focused coping). The current study, alongside other extant research (e.g., Brimmell et al, 2019), demonstrates that the DRES has utility in predicting performance and therefore theorists should more closely consider the role of coping in challenge and threat states. Indeed, the DRES has been shown to predict performance in a range of contexts in the laboratory (e.g., Vine et al, 2013), and in more ecologically valid settings similar to the current study, such as sport (Moore et al, 2013), aviation (e.g., Vine et al, 2015), and medicine (e.g., Roberts et al, 2016).…”
Section: Discussionsupporting
confidence: 57%
“…Some contemporary challenge and threat theory (such as the TCTSA) does not include coping in its Lazarusian form (i.e., emotion focused and problem focused coping). The current study, alongside other extant research (e.g., Brimmell et al, 2019), demonstrates that the DRES has utility in predicting performance and therefore theorists should more closely consider the role of coping in challenge and threat states. Indeed, the DRES has been shown to predict performance in a range of contexts in the laboratory (e.g., Vine et al, 2013), and in more ecologically valid settings similar to the current study, such as sport (Moore et al, 2013), aviation (e.g., Vine et al, 2015), and medicine (e.g., Roberts et al, 2016).…”
Section: Discussionsupporting
confidence: 57%
“…This indicates that evaluations and physiological responses to challenge and threat operated in separation. Although this finding contradicts the theory (Blascovich 2008), it is in line with some previous studies that revealed a non-significant relationship between CO and TPR, and challenge/threat evaluation (Behnke et al 2020;Brimmell et al 2019). This might result from the fact that physiological responses are mainly influenced by the homeostatic mechanisms and depend on several factors with stress appraisal being only one of them (Levenson 2014).…”
Section: Discussionsupporting
confidence: 79%
“…Precisely, the BPSM states that feedback during and after the motivated performance situation is used to update task demand and coping resource evaluations. A recent study supported this prediction, finding that performance in the first part of a motivated performance situation was positively associated with demand-resource evaluations in anticipation of the second part of the motivated performance situation, where better performance predicted evaluations more consistent with a challenge state (Brimmell et al, 2019). The BPSM also states that task disengagement occurs when demand evaluations extremely outweigh resource evaluations (or vice versa).…”
Section: Integrating Blunted Cvr To Stress Into the Bpsmmentioning
confidence: 88%